Своєрідність образу пропащої жінки в російській літературі XIX ст. (на прикладі творів Ф. Достоєвського та Л. Толстого) - Мартинець, Алла Михайлівна (Східноєвропейський національний університет імені Лесі Українки, 2013)
Статтю присвячено дослідженню образу пропащої жінки в російській літературі XIX ст. на прикладі романів Ф. Достоєвського «Злочин і кара» та Л. Толстого «Воскресіння». Вказано на закономірності виникнен-ня образу та його функціонування. Проаналізовано погляди вчених на цю дефініцію і доведено своєрідність образу прикладами з тесту. The article studies the image of the fallen woman in the Russian literature of the XIX century by the example of Dostoevskyʼs novel «Crime and Punishment» and Tolstoyʼs «Resurrection»/ Having analyzed a number of studies we can conclude that the image of fallen woman differs from the images of courtesans or prostitutes. Her fall is usually influenced by such factors as society, the life condition, family. Fallen woman often does not have another choice except to break the habitual way, scandalously neglect accepted rules, selling themselves in sexual slavery. The image of the fallen woman absorbed the impact of times and society, undergoing aesthetic, philosophical, and political influence. In works of art this image performs a variety of functions – from frustration and requests for assistance to the protests and attempts to «save souls» who are close by. The image is manifested at different levels: plot-compositional, aesthetic, problem-themed. To create this image writers usually prefer elements of psychoanalysis and internal monologue. Artistic detail is considered to be one of the most important basis for creating an artistic image.
Keywords: образ пропащої жінки; роман; реалізм; психоаналіз